GIVING BEHAVIOUR IN JAKARTA: ROLE OF KNOWLEDGE ON ISLAMIC CHARITY - prasetyawan, wahyu; Nasyiyatul Aisyiyah, Denis (Jurnal Manajemen Dakwah, 2025)
This study examines the relationship between knowledge of Islamic charitable teachings and the intention to donate among Muslims in Jakarta, utilising the Theory of Planned Behaviour. Survey data from 100 Muslim respondents reveal that knowledge of zakat, sadaqah, and related practices strongly correlates with the intention to give, while socio-demographic factors such as income, gender, and education show no significant associations. Employing Ordinary Least Squares regression, the analysis highlights the importance of religious education and informal Islamic education, such as Majelis Taklim study circles, in promoting charitable behaviour. These findings suggest that enhancing dissemination of Islamic charitable knowledge may encourage greater philanthropic participation within Muslim communities in Jakarta. The study provides new insight into the motivational role of religious knowledge in charitable giving, contrasting with conventional focus on socio-economic variables. Recommendations include expanding sample size and exploring wider socio-cultural influences on donation behaviour.   Kata kunci: Behavior, Knowledge, Islamic Charity   Studi ini mengkaji hubungan antara pengetahuan tentang ajaran amal Islam dan niat berdonasi di kalangan Muslim di Jakarta, dengan menggunakan Teori Perilaku Terencana. Data survei dari 100 responden Muslim menunjukkan bahwa pengetahuan tentang zakat, sedekah, dan praktik terkait berkorelasi kuat dengan niat berdonasi, sementara faktor sosiodemografi seperti pendapatan, gender, dan pendidikan tidak menunjukkan hubungan yang signifikan. Dengan menggunakan regresi Ordinary Least Squares, analisis ini menyoroti pentingnya pendidikan agama dan pendidikan Islam informal, seperti majelis taklim, dalam mendorong perilaku beramal. Temuan ini menunjukkan bahwa peningkatan penyebaran pengetahuan amal Islam dapat mendorong partisipasi filantropi yang lebih besar dalam komunitas Muslim di Jakarta. Studi ini memberikan wawasan baru tentang peran motivasional pengetahuan agama dalam beramal, yang berbeda dengan fokus konvensional pada variabel sosial-ekonomi. Rekomendasi yang diberikan meliputi perluasan ukuran sampel dan eksplorasi pengaruh sosial-budaya yang lebih luas terhadap perilaku berdonasi.   Kata kunci: Perilaku, Pengetahuan, Amal Islam